Deictics and the construction of mathematics and science knowledge in the secondary school classroom. Issue 2 (4th May 2017) - Hansen-Thomas, Holly; Langman, Juliet
Abstract: Taking a Teacher Language Awareness (TLA) perspective, this paper examines how the concept of deixis is employed in oral discourse in two secondary science and mathematics classes in the southwestern part of the US. Drawing on audio and videotaped data from two classrooms, we examine how verbal deixis, or words and phrases that cannot be fully understood without additional context, serves as a potential resource for the organisation of learning processes. We further consider how deixis may act as an impediment to the organisation of learning processes. We outline implications for preparation of teachers of English Language Learners in Science, Technology, Engineering and Mathematics areas, with a specific focus on middle and high school science and mathematics.